Tipping into the abyss: with more than a virtual parachute? - Chris Tompsett (Association for Learning Technology, 2007)
Any application of information and communication technology in education (ICTE) sits, at times uncomfortably, at the intersection of three key disciplines: technology, education and sociology (including reflexivity). To confuse matters, any specific study may need to take account of specific knowledge within subdisciplines, such as organisational management and technology transfer, and of knowledge within the domain of application (e.g. nursing, social work, fashion, etc.). Researchers must build a consistent model of knowledge that can integrate disparate methodologies, research goals and even conflicting interpretations of the same terminology. Without this, the ICTE research field will be dominated by what is simply novel, irrespective of the relevance of particular changes to educational practice. If existing models in this field are as limited as suggested by Moule, when should lecturers and teachers, with no motivation to use technology for its own sake and no additional financial support, review progress in this field for effective examples of innovative practice, let alone wide-scale change? On most of the criteria that could be introduced to compare two papers, the views of Moule and Salmon appear almost diametrically opposed and a detailed comparison would seem of limited value. Instead, this paper asks a more fundamental question: what could be the basis within this research community for establishing coherence within the field and ensuring that research can justify actual changes in educational practice?